Sports injuries in the emergency department: an observational study with a gender perspective - Sandra Mallorquín; Luis Martínez-Sañudo; Maribel González-Riveiro; Mireia Viñas-Noguera; Maria del Mar Pizà-Serra; Xavier Pelfort-López (International Journal of Emergency Medicine)
Abstract Introduction Sports injuries are a significant concern in emergency departments and affect both amateur and professional athletes. With the increase in women’s participation in sports, it is crucial to understand sex-specific injury characteristics, as patterns observed in men may not apply to women. This observational, descriptive and retrospective study aims to analyze sex differences in sports injuries to improve diagnosis, treatment, and prevention strategies. Our hypothesis is that sports injury patterns differ between sexes. Methods Patients treated for sports injuries between 2020 and 2023 in the Emergency Department at our hospital were included in the study. Researchers collected data on demographics, sports practiced, types of injuries, and initial treatment, utilizing descriptive statistics, Student’s t-test for continuous variables, Fisher’s exact test for categorical variables, and variable correlation for data analysis. Results A total of 977 patients were included in the study, 82% of whom were men. Significant differences were observed regarding the sport practiced (p < 0.001) and the type of injury (p = 0.02) between the groups. No differences were observed in injury location or the percentage of patients receiving each treatment modality. Specific correlations were also conducted between sports, type of injury, and location. Contusions, ligamentous injuries and dislocations were associated with specific sports and/or locations in men and women. Ligamentous injuries were observed in both sexes predominantly in the ankle and knee. Conclusion Increasing sports participation offers health benefits but also increases the risk of injuries. Our study aimed to investigate whether sports injury patterns differ between sexes. The results support this hypothesis, highlighting significant sex differences in injury patterns.